PERAN GURU DALAM PEMBENTUKAN KARAKTER RELIGIUS ANAK USIA DINI - Imelda T. Kase; Fredericksen Victoranto Amseke (PT. Jurnal Center Indonesia Publisher, 2024)
Religious character is an aspect of personality that is instilled in children from an early age in the task of moral and religious development. The aim of the research is to determine the role of teachers in forming the religious character of early childhood children aged 4 - 6 years at PAUD Taruna Elim Kuanino, Kupang City. Religious character is a character value in relation to God and is shown in a person's thoughts, words and actions based on divine values ​​and religious teachings. The research method used is a qualitative research method. Data collection techniques through observation, interviews and documentation. The results of the research show that the formation of religious character values ​​in the aspect of worship values ​​is carried out by habituation such as praying before carrying out activities and singing and carrying out activities related to religious character, the formation of religious character in the aspect of disciplinary values ​​related to obedience, obedience and order, the formation of religious character In the aspect of exemplary values, it is applied by being polite in front of children, saying sorry when you make a mistake, saying please when asking for help, saying thank you when you receive something. Habituation methods such as praying before carrying out activities and memorizing prayers and greeting others. Method of telling children about religious and moral values ​​to improve religious character. The field trip method is carried out by visiting places of worship such as mosques and churches.